Processed airborne radio-echo sounding data from the AGAP survey covering Antarctica's Gamburtsev Province, East Antarctica (2007/2009) - Corr, Hugh; Ferraccioli, Fausto; Jordan, Tom; Robinson, Carl (NERC EDS UK Polar Data Centre, 2021)
An airborne radar survey was flown as part of the seven nation Antarctica's Gamburtsev Province (AGAP) expedition over the Gamburtsev Subglacial Mountains, Dome A, and the interior of East Antarctica during the International Polar Year 2007-2009. Operating from field camps located on either side of Dome A (namely AGAP-N and AGAP-S), we collected ~120,000 km (equivalent to 180,000 km2) of airborne survey data using two Twin Otter aircrafts - one from BAS and one from the United States Antarctic Program (USAP). The aircrafts were equipped with dual-frequency carrier-phase GPS for navigation, laser ranging systems, magnetometers, gravity meters, and ice-sounding radars. We present here the full radar dataset from the BAS PASIN radar system consisting of the deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the navigational information of each trace, the surface and bed elevation picks, ice thickness, and calculated absolute surface and bed elevations. This dataset comes primarily in the form of NetCDF and georeferenced SEGY files. To interactively engage with this newly-published dataset, we also created segmented quicklook PDF files of the radar data. : ** Instrumentation and Processing: Radar data were collected using the bistatic PASIN radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using two interleaved pulses: a 4-microseconds, 12 MHz bandwidth linear chirp (deep sounding) and a 0.1-microseconds unmodulated pulse (shallow sounding). Chirp compression was applied using a Blackman window to minimise sidelobe levels, resulting in a processing gain of 10 dB. For the chirp data, 2-D Synthetic Aperture Radar (SAR) processing based on the Omega-K algorithm was applied to the data to enhance both along-track resolution and echo signal noise (see Heliere et al., 2007). An additional incoherent averaging filter along a moving window of length 9 was also applied to the chirp data. This data is best used to assess the bed and internals in deep ice conditions. The pulse data was processed using an incoherent averaging filter along a moving window of length 25 and using a combination of the upper and lower channels. This data is best used to assess the internal structure and bed in shallow ice conditions. Note that the chirp and pulse products for this survey are not the same size (see below for more details). The bed reflector was first automatically depicted on the chirp data using a semi-automatic picker in the PROMAX software package. All the picks were afterwards checked and corrected by hand if necessary. The picked travel time was then converted to depth using a radar wave speed of 168 m/microseconds and a constant firn correction of 10 m. Surface elevation is derived from radar altimeter for ground clearance < 750 m, and the PASIN system for higher altitudes. Note: Small (a few minutes) time jumps are contained in a limited number of survey lines as a result of the re-booting of the PASIN system. ** Coordinates and Positions: The coordinates provided in the NetCDF for the surface and bed elevation for each radar trace are in longitude and latitude (WGS84, EPSG: 4326). The navigation attributes for the radar data in the NetCDF are in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin: 0.994 False easting: 0 False northing: 2082760.109 The coordinates in the SEGY data are also in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), although note that these are in integer format due to the SEGY limitations (see section below). Positions are calculated for the phase centre of the aircraft antenna. All positions (Longitude, Latitude and Height) are referred to the WGS1984 ellipsoid. ** Dataset: Please note: Due to the unstable nature of SEGY-formatted data and its uncertain long-term future, as well as the issues documented below, we also provide the full radar data in NetCDF format. The dataset provided here consists of three parts: a NetCDF file per flightline, two SEGY files per flightline (one chirp and one pulse), and one quicklook PDF file per flightline. These are described in more details below. - NetCDF: The NetCDF files contain the deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the associated metadata, navigational information (in both EPSG: 3031 and WGS84 EPSG: 4326), and the associated radar-related information for each trace (e.g. surface/bed elevation and picks, ice thickness, aircraft altitude, range to surface, time of trace) which are provided as separate attributes in the NetCDF file. The navigational position of each trace comes from the surface files, and the processed GPS files when no surface information was provided in the surface files. Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. No data is shown as "-9999" throughout the files. Please note: Care must be taken when comparing both the chirp and pulse radar data arrays due to varying lengths. Due to issues in the packaging and processing of the two radar products, the trace number differs between both data sets. The only way to compare the chirp and pulse radar products is to use the 2x PriNumber variables ('PriNumber_chirp' and 'PriNumber_pulse') stored in the NetCDF files. The other one dimensional variables ending in "_layerData" in the NetCDF are aligned to the 'pulse_data' variable (see below for more details). NetCDF attributes: - 'traces_chirp': Trace number for the chirp radar data (x axis) - 'traces_pulse': Trace number for the pulse radar data (x axis) - 'fast_time': Two-way travel time (y axis) (units: microseconds) - 'x_coordinates': Cartesian x-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'y_coordinates': Cartesian y-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'chirp_data': Radar data for the processed (incoherent) SAR chirp (units: power in dBm) - 'pulse_data': Radar data for the processed (incoherent) pulse (units: power in dBm) - 'PriNumber_chirp': Incremental integer reference number related to initialisation of the radar system that permits processed chirp SEGY data and picked surface and bed to be linked back to raw radar data (also known as PriNum) (units: arbitrary - integers) - 'PriNumber_pulse': Incremental integer reference number related to initialisation of the radar system that permits processed pulse SEGY data and picked surface and bed to be linked back to raw radar data (also known as PriNum) (units: arbitrary - integers) - 'longitude_layerData': Longitudinal position of the trace number (units: degree_east in WGS84 EPSG:4326) - 'latitude_layerData': Latitudinal position of the trace number (units: degree_north in WGS84 EPSG:4326) - 'UTC_time_layerData': Coordinated Universal Time (UTC) of trace (also known as resTime) (units: seconds) - 'terrainClearanceAircraft_layerData': Terrain clearance distance from platform to air interface with ice, sea or ground (also known as resHt) (units: meters) - 'aircraft_altitude_layerData': Aircraft altitude (also known as Eht) (units: meters relative to WGS84 ellipsoid) - 'surface_altitude_layerData': Ice surface elevation for the trace number from radar altimeter and LiDAR (units: meters relative to WGS84 ellipsoid) - 'surface_pick_layerData': Location down trace of surface pick (BAS system) (units: microseconds) - 'bed_altitude_layerData': Bedrock elevation for the trace number derived by subtracting ice thickness from surface elevation (units: meters relative to WGS84 ellipsoid) - 'bed_pick_layerData': Location down trace of bed pick (BAS system) (units: microseconds) - 'land_ice_thickness_layerData': Ice thickness for the trace number obtained by multiplying the two-way travel-time between the picked ice surface and ice sheet bed by 168 m/microseconds and applying a 10 meter correction for the firn layer (units: meters) - SEGY: The SEGY files are provided for both the chirp and pulse-acquired data and have been georeferenced using the navigational position of each trace from the surface files, and the processed GPS files when no surface information was provided in the surface files. Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. Please note: Care must be taken when comparing the chirp and pulse SEGY data directly. Due to issues mentioned above, the chirp and pulse data have a different amount of traces and thus different lengths. Use the XY coordinates associated to each trace for direct comparison of the two SEGY files (if using seismic software in geospatial window), or the 2x PriNumber variables ('PriNumber_chirp' and 'PriNumber_pulse') in the NetCDF if reading in the files programmatically. To associate the XY information found in the NetCDF into each trace of the chirp radar product, one must use the nearest PriNumber from the chirp SEGY with the PriNumber from the pulse SEGY and find the associate XY values for that specific PriNumber. Note that this issue does not affect the other NetCDF 1-D variables ending in '_layerData' as they are aligned to the pulse data. SEGY header description: - byte number 1-4 and 5-8 (SEQWL and SEQWR): Trace number for each SEGY trace - byte number 9-12 (FFID): PriNumber for each SEGY trace - byte number 73-76 (SRCX): Cartesian x-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 77-80 (SRCY): Cartesian y-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 115-116 (NSMP): Number of samples for each SEGY trace - byte number 117-118 (SI): Sampling interval for each SEGY trace Note that the current version of the SEGY (Revision 1.0) does not yet allow to store double-precision floats in the "Source X/Y" trace headers and thus the X and Y positions for each trace are rounded to the nearest integer when exporting the data. This will affect the accurate position of each trace in the SEGY data, however the precise X and Y position of each trace can be obtained from the NetCDF files if necessary. When loading in the georeferenced SEGY files into seismic-interpretation software for data visualisation and analysis, the user might be warned that duplicate traces are found within the data and that this might cause "bad performance". This is caused by the rounding of the X and Y positions in the SEGY headers as explained above and should only affect the position of a relatively small amount of traces. - Quicklook: The quicklook PDF files were produced to allow for a quick visualisation of the radar data and the position of each flightline with regards to the rest of the survey flightlines. The radar image in the PDF is from the processed chirp radar data and is split into 50-km segments for the AGAP survey. These segments (and the radar images associated with them) are the same as those shown on the Polar Airborne Geophysics Data Portal. : ** Instrument: Radar data were collected using the bistatic PASIN (Polarimetric radar Airborne Science Instrument) radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using two interleaved pulses: a 4-microseconds, 12 MHz bandwidth linear chirp (deep sounding) and a 0.1-microseconds unmodulated pulse (shallow sounding). The Pulse Repetition Frequency was15,625 Hz (pulse repetition interval: 64 microseconds). ** Antenna configuration: 8 folded dipole elements: 4 transmitters (port side) 4 receivers (starboard side) Antenna gain: 11 dBi (with 4 elements) Transmit power: 1 kW into each 4 antennae Maximum transmit duty cycle: 10% at full power (4 x 1 kW) ** Radar receiver configuration: Receiver vertical sampling frequency: 22 MHz (resulting in sampling interval of 45.4546 ns) Receiver coherent stacking: 25 Receiver digital filtering: -50 dBc at Nyquist (11 MHz) Effective PRF: 312.5 Hz (post-hardware stacking) Sustained data rate: 10.56 Mbytes/second : - Trace spacing (post-processed data): ~20 m - Vertical resolution: ~8.4 m - Radar centre frequency: 150 MHz - Radar bandwidth: 12 MHz - Radar Receiver vertical sampling frequency: 22 MHz - Absolute GPS positional accuracy: <1.0 m (relative accuracy is one order of magnitude better). Banking angle was limited to 10 deg during aircraft turns to avoid phase issues between GPS receiver and transmitter. Flights were flown in a detailed survey grid with a line spacing of ~5 km and tie lines ~33 km apart. Crossover analysis of the bed pick data along flight lines reveals RMS differences of ~64 m in bed elevation with a mean of 74 m, which primarily results from off-nadir reflections and interpretation/digitizing uncertainty. Please note: The surface and bed pick information (surface and bed elevation, ice thickness, etc.) from both the BAS and USAP components of the radar survey can also be found at: https://doi.org/10.5285/0f6f5a45-d8af-4511-a264-b0b35ee34af6.